1991
DOI: 10.1042/cs0800633
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure in chronic cardiac failure

Abstract: 1. Resting energy expenditure has previously been shown to be elevated in the acute phase of heart failure, but the situation in the compensated state of chronic cardiac failure is unclear. Resting energy expenditure was assessed in 14 patients with stable chronic cardiac failure and 14 matched control subjects by using indirect calorimetry. 2. Resting energy expenditure was significantly elevated in the patients with chronic cardiac failure (112.6 +/- 18.1 versus 87.1 +/- 12.2 kJ day-1 kg-1 total body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 16 publications
2
44
1
Order By: Relevance
“…Recent reports from our laboratory (Poehlman et al, 1994;Obisesan et al, 1996) and others (Riley et al, 1991) showed elevations in resting energy expenditure in stabilized heart failure patients. Additionally, we reported that resting energy needs increased with symptom severity (Obisesan et al, 1996).…”
Section: Discussionmentioning
confidence: 84%
“…Recent reports from our laboratory (Poehlman et al, 1994;Obisesan et al, 1996) and others (Riley et al, 1991) showed elevations in resting energy expenditure in stabilized heart failure patients. Additionally, we reported that resting energy needs increased with symptom severity (Obisesan et al, 1996).…”
Section: Discussionmentioning
confidence: 84%
“…The determination of REE is important for the establishment of energy recommendations and maintenance of nutritional balance of the individuals . Elevated REE has been pointed out as a contributory factor for cachexia in several disease conditions (Riley et al, 1991;Falconer et al, 1994) and an association with mortality has been suggested (Wang et al, 2004). However, little is known about REE and its determinants in chronic kidney disease (CKD) patients undergoing hemodialysis (HD).…”
Section: Introductionmentioning
confidence: 99%
“…Peak oxygen consumption (peak VO 2 ) was defined as the highest VO 2 value averaged over 15 seconds during the final minute of exercise. [17][18][19][20] Statistics: All date are were expressed as the mean±standard deviation (SD). A value of p<0.05 was considered statistically significant.…”
Section: )mentioning
confidence: 99%